Comparative Analysis of Household Composting Methods for Organic Waste Management (Padmakanya Journal of Science and Technology, 2025)
Solid waste management remains a major environmental challenge in Nepal, particularly in urban centers like the Kathmandu Valley, where organic waste makes up over 50% of municipal solid waste. This study compares the effectiveness of three household-level composting methods—vermicomposting, Takakura composting, and plastic bag composting—by evaluating their decomposition rates, nutrient yields, and key physicochemical properties. Using 700g of vegetable and fruit peels per method, composting was carried out in cardboard boxes, and final composts were analyzed for temperature, pH, moisture content, electrical conductivity, water-holding capacity, organic matter, nitrogen content, and carbon-to- nitrogen (C:N) ratio. Statistical analysis (Kruskal-Wallis H test and Tukey’s Post Hoc test) revealed significant differences in several parameters, including moisture, water-holding capacity, and nitrogen content. Takakura composting yielded the fastest decomposition time (51 days) and highest organic matter content (41.60%), while vermicomposting produced the highest nitrogen content (2.83%), water-holding capacity (82%), and overall yield (391g). Box composting performed least effectively across most parameters. The findings suggest Takakura composting is best suited for rapid, small-scale household composting, whereas vermicomposting is ideal for high-yield, nutrient-rich compost production on a household or commercial scale. Overall, the study underscores the potential of decentralized composting as a sustainable solution for organic waste management in Nepal.